Generalized Baer rings - Tai Keun Kwak (International Journal of Mathematics and Mathematical Sciences)
We investigate the question whether the p.q.-Baer center of a ring R can be extended to R. We give several counterexamples to this question and consider some conditions under which the answer may be affirmative. The concept of a generalized p.q.-Baer property which is a generalization of Baer property of a ring is also introduced.